Design and implementation of a cluster virtualization based fine snapshot system - XIANG Xiao-jia; SHU Ji-wu; YU Hong-liang (Tongxin xuebao)
A fine snapshot technology in volume level was presented which could be used to keep old data flexibly and frequently,to recovery from deletion,to limit exposure to data lose for logic volumes.First,two kinds of logic volumes namely,checkpoint and finesnap were designed and used as containers of snapshot data.Linking checkpoint volumes and finesnap volumes together by the order of time could make up of a hybrid snapshot chain,with which both good per-formance and high efficiency on storage usage were available.Second,a bitmap in each finesnap volume to accelerate data searching and reduce the memory exhausted was incorporated.Evaluation results from representative experiments demonstrate that the prototype system,named LV-Fine,has the ability to provide good performance,and to introduce less storage overhead than LVM2,the famous cluster virtualization system.